Moral Judgment, Sensitivity To Reasons, and the Multi-system View - Francesco Orsi (Baltic International Yearbook of Cognition, Logic and Communication, 2012)
In this paper I attempt a critical examination of the multi-system or dual-process view of moral judgment. This view aims to provide a psychological explanation of moral sensitivity, and in particular an explanation of conflicting moral sensitivities in dilemma cases such as the crying baby scenario. I argue that proponents of the multi-system view owe us a satisfactory account of the mechanisms underlying “consequentialist” responses to such scenarios. For one thing, the “cognitive” processes involved in consequentialist reasoning only seem to play a subserving role with respect to the final judgment (providing non-moral inputs to judgment, or exerting additional strength to override the immediate “deontological” response). In this sense, Greene and colleagues fail to identify a peculiar system of moral judgment specularly opposed to the affective “deontological” one. For another, Greene and colleagues’ work on the emotion-cognition dichotomy and the distinction between alarm-bell and currency emotions, though promising, still falls short of providing an adequate and consistent picture of the psychological mechanisms underlying “cognitive” evaluations and verdicts in dilemma scenarios. It is suggested that alongside further experimental work, proponents of this view should pay more attention to the conceptual underpinnings of their distinctions.